2000
DOI: 10.1111/j.1439-0388.2000x.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative genetic approach for the investigation of ageing grey horse melanoma

Abstract: Ageing grey horses are particularly susceptible to melanoma. Using segregation analysis, six genetic and nongenetic (environmental) models in two grey horse family groups (n = 71) were compared. The polygenic model still fits the data significantly better than an environmental model, indicating a strong genetic impact on the phenomenon. Pmel17/gp100 and TYRP1/gp75, two genes which are specific for melanocytes, and Cdkn2a/p16 a gene coding for an inhibitor of a cell cycle regulator were partially cloned, sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 25 publications
2
33
1
Order By: Relevance
“…In greying level (L*) an odds of melanoma occurrence was estimated to be 1.11 times higher. The estimated higher odds of melanoma occurrence for a higher greying level contradicts the assumption that the loss of pigment need not be a cause of the appearance of dermal melanoma (Rieder et al, 2000;Hofmanová et al, 2010). Table 4 shows the estimations of variance components based on LM, TM, and TMb models.…”
Section: Analysis Of Environmental Effectscontrasting
confidence: 41%
See 2 more Smart Citations
“…In greying level (L*) an odds of melanoma occurrence was estimated to be 1.11 times higher. The estimated higher odds of melanoma occurrence for a higher greying level contradicts the assumption that the loss of pigment need not be a cause of the appearance of dermal melanoma (Rieder et al, 2000;Hofmanová et al, 2010). Table 4 shows the estimations of variance components based on LM, TM, and TMb models.…”
Section: Analysis Of Environmental Effectscontrasting
confidence: 41%
“…On the other hand, Rieder et al (2000) and Hofmanová et al (2010) found the influence of L value on melanoma occurrence to be statistically not significant at the evaluation on the same significance level (P < 0.05).…”
Section: Analysis Of Environmental Effectsmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, other traits of significance such as coat color, etc., can be better addressed by understanding the molecular cause of variation in expression. Recent studies have shown that the mouse cannot be 'taken for granted' as a model animal for all human conditions (Rieder et al 2000;Heinzerling et al 2001), and that in some cases, the horse can be a better model (Rieder et al 2000).…”
Section: Tammen]mentioning
confidence: 99%
“…It is, nowadays, accepted as a true neoplasm (Gorham and Robl 1986, Macgillivray et al 2002, PattersonKane and Ginn 2003, Seltenhammer et al 2004. Several research groups have investigated the genetic basis of melanoma formation and found a link between the autosomal dominant trait of greying with age and melanoma formation in horses (Rieder et al 2000, Seltenhammer et al 2003, Rosengren Pielberg et al 2008, Sundstrom et al 2012). …”
Section: Introductionmentioning
confidence: 99%